A constituição pedagógica do direito ambiental - Martins, Ezequiel (My University, 2014)
This work focuses the importance of the environmental education, starting from several currents. The objective is it of developing a critical spirit starting from these currents, demonstrating the crisis of conceptions at the present time. The dualism is questioned between the conceptions antropocêntricas and ecocêntricas seeking encampar an ethics gone back to the holismo. Many of the currents of environmental education have not been so profícuas with its objectives and proposed results. Of there that the theme should be faced with an inclination sistêmico in order to contribute, if possible, with the efetivação of the Environmental Right. The logicalsystematic interpretation of the used legal texts is adopted in order to look for a vision integradora being avoided a posture positivista of the reality. It is revealed urgent to learn and reaprender concepts of environmental education, as form of looking for the unit of the knowledge, conjugated with the multiplicity of the you know. To approach the Law n° 9.795, of April 27, 1999 (law of environmental education) that, to the everything indicates, it is not capable of, by itself, to educate the human being before in society to the demands and complexities of the present time. The theory sistêmica is focused as form of understanding of the social, conceived phenomenon the Environmental Right as subsistema of the social system and its relationships with the environmental education. It is questioned on which the possible relationship between the a community's education and the efetivação of the norm of the environmental right and as it happens the process of the pedagogic constitution under the optic sistêmica. Discorre-if on the juridical principles of protection of the environment in face of the art. 225 of the Federal Constitution.
Este trabalho enfoca a importância da educação ambiental, a partir de diversas correntes. O objetivo é o de desenvolver um espírito crítico a partir destas correntes, demonstrando a crise de concepções na atualidade. Questiona-se o dualismo entre as concepções antropocêntricas e ecocêntricas visando encampar uma ética voltada para o holismo. Muitas das correntes de educação ambiental não têm sido tão profícuas com os seus objetivos e resultados propostos. Daí que o tema deve ser enfrentado com um viés sistêmico a fim de contribuir, se possível, com a efetivação do Direito Ambiental. Adota-se a interpretação lógico-sistemática dos textos legais utilizados a fim de buscar uma visão integradora evitando-se uma postura positivista da realidade. Revela-se urgente aprender e reaprender conceitos de educação ambiental, como forma de buscar a unidade do conhecimento, conjugada com a multiplicidade dos saberes. Abordar-se a Lei n° 9.795, de 27 de abril de 1999 (lei de educação ambiental) que, ao tudo indica, não é capaz de, por si só, educar o ser humano em sociedade ante às exigências e complexidades da atualidade. Enfoca-se a teoria sistêmica como forma de compreensão do fenômeno social, concebido o Direito Ambiental como subsistema do sistema social e sua relações com a educação ambiental. Questiona-se sobre qual a relação possível entre a educação de uma comunidade e a efetivação da norma do direito ambiental e como ocorre o processo da constituição pedagógica sob a ótica sistêmica. Discorre-se sobre os princípios jurídicos de proteção do meio ambiente em face do art. 225 da Constituição Federal.
Keywords: Direito; Meio ambiente; Correntes de educação ambiental; Princípios; Holismo; Pensamento sistêmico; Educação ambiental; Environment; Environmental education; Principles; Holism; Systemic Thougt